2013
DOI: 10.1371/journal.pone.0060864
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Vitamin D Status in Fair-Skinned Women of Childbearing Age at Northern Latitudes

Abstract: Background and ObjectivePoor vitamin D status during pregnancy has been associated with unfavorable outcomes for mother and child. Thus, adequate vitamin D status in women of childbearing age may be important. The aim of this study is to investigate the determinants of 25-hydroxyvitamin D (25(OH)D) serum concentrations in women of childbearing age living in Sweden, at latitude 57–58° north.MethodEighty four non-pregnant, non-lactating, healthy, fair-skinned women aged between 25–40 years were included. All sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
22
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 36 publications
9
22
1
Order By: Relevance
“…Similarly, mean 25(OH)D concentrations were higher in the third trimester than in early pregnancy during all seasons except winter, perhaps due to the small group sampled in early pregnancy during winter. We have previously showed that use of estrogen contraceptives is associated with higher 25(OH)D concentrations in non-pregnant women of childbearing age [29]. Similar hormonal changes due to pregnancy cannot be ruled out as a cause of the increasing 25(OH)D concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, mean 25(OH)D concentrations were higher in the third trimester than in early pregnancy during all seasons except winter, perhaps due to the small group sampled in early pregnancy during winter. We have previously showed that use of estrogen contraceptives is associated with higher 25(OH)D concentrations in non-pregnant women of childbearing age [29]. Similar hormonal changes due to pregnancy cannot be ruled out as a cause of the increasing 25(OH)D concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of serum 25(OH)D was affected by many factors such as season or the extent of exposure to UV-B radiation, use of vitamin D supplements, intake of diets rich in vitamin D and use of estrogen contraceptives as well as the difference between urban and rural areas (Table 3 and Table 4) [30, 3336]. There was higher serum vitamin D level of lactating women in urban area than in rural area in Beijing, which might be due to the difference of multivitamin supplement uses as well as the intake of food rich in vitamin D [33].…”
Section: Discussionmentioning
confidence: 99%
“…There was higher serum vitamin D level of lactating women in urban area than in rural area in Beijing, which might be due to the difference of multivitamin supplement uses as well as the intake of food rich in vitamin D [33]. Season is an important factor in determining vitamin D status of lactating women which could be related to sunlight exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Danish adults in general, 52% have a 25(OH)D below 50 nmol/l . In two smaller Scandinavian studies of young women, however, only 16–23% had 25(OH)D below 50 nmol/l …”
mentioning
confidence: 96%